Insights into the Landscape of Alphavirus Receptor and Antibody Interactions - Shishir Poudyal; Abhishek Bandyopadhyay; Richard J. Kuhn (Viruses, 2025)
Alphaviruses engage a diverse array of attachment factors and receptors during viral entry, resulting in a broad host range and disease spectrum, and thus presenting them as a major global public health concern. The development of effective antivirals against these arboviruses relies on a comprehensive understanding of the molecular interplay between these viruses and host cell factors, as well as the wide range of immune responses that ensue following viral infection. In this review, we present the current understanding of the complex landscape of alphavirus interaction with attachment factors and entry receptors, some of which are characterized structurally, while others are characterized biochemically. Additionally, we provide an overview of the molecular bases of epitope recognition by neutralizing and non-neutralizing antibodies against alphaviruses, and how icosahedral symmetry influences these interactions, such as occupancy and neutralization potency. We further discuss the structural bases of epitope recognition of a few pan-alphavirus antibodies, their potential therapeutic implications, and offer future perspectives on the development of effective therapeutics against clinically relevant alphaviruses.